Pulse shape discrimination in an organic scintillation phoswich detector using machine learning techniques - Lee, Yujin; Kim, Jinyoung; Koh, Byoung-cheol; Yoon, Young Soo; Ha, Chang Hyon (Frontiers in Physics, 2024)
We developed machine learning algorithms for distinguishing scintillation signals from a plasticliquid coupled detector known as a phoswich. The challenge lies in discriminating signals from organic scintillators with similar shapes and short decay times. Using a single-readout phoswich detector, we successfully identified γ radiation signals from two scintillating components. Our Boosted Decision Tree algorithm demonstrated a maximum discrimination power of 3.02 ± 0.85 standard deviation in the 950 keV region, providing an efficient solution for self-shielding and enhancing radiation detection capabilities.